Brief Remote Intervention to Manage Food Cravings and Emotions During the COVID-19 Pandemic: A Pilot Study - Devonport, Tracey J.; Chen-Wilson, Chao-Hwa; Nicholls, Wendy; Robazza, Claudio; Cagas, Jonathan Y.; Fernández-Montalvo, Javier; Choi, Youngjun; Ruiz, Montse C. (Frontiers in Psychology, 2022)
As a result of the COVID-19 pandemic people have endured potentially stressful challenges which have influenced behaviors such as eating. This pilot study examined the effectiveness of two brief interventions aimed to help individuals deal with food cravings and associated emotional experiences. Participants were 165 individuals residing in United Kingdom, Finland, Philippines, Spain, Italy, Brazil, North America, South Korea, and China. The study was implemented remotely, thus without any contact with researchers, and involved two groups. Group one participants were requested to use daily diaries for seven consecutive days to assess the frequency of experience of their food cravings, frequency of giving in to cravings, and difficulty resisting cravings, as well as emotional states associated with their cravings. In addition to completing daily food diaries, participants in group two were asked to engage in mindful eating practice and forming implementation intentions. Participants assessed their perceived changes in eating, wellbeing, and health at the beginning and end of the intervention. Repeated measures MANOVAs indicated that participants experienced significantly less food cravings (i.e., craving experience, acting on cravings, difficulty resisting), as well as lower intensities of unpleasant states associated with cravings across time (T1 vs. T7). In contrast to our hypothesis, the main effects of the group (food craving diary vs. food craving diary and mindful eating practice) were not significant. Participants reported less eating and enhanced wellbeing at the end of the study (T7 vs. T1). Our findings can be used to inform future remote interventions to manage food cravings and associated emotions and highlight the need for alternative solutions to increase participant engagement.